Preliminary analysis of qEEG during a subliminally‐primed task‐switching test in pre‐symptomatic Alzheimer's disease. (31st December 2021) - Wu, Daw‐An; Adams, Sara W.; Hung, Shao‐Min; Rossi, Iyla P.; Harrington, Michael G.; Shimojo, Shinsuke; Arakaki, Xianghong
Abstract: Background: In testing cognitively healthy (CH) participants with normal vs. pathological amyloid/tau ratios (CH‐NAT vs. CH‐PAT), we previously identified significant differences in alpha‐band markers from quantitative electroencephalography (qEEG) during a Stroop‐based task‐switching test. Using a modified version of the test, we then found that CH‐PATs and CH‐NATs were differentially susceptible to subliminal priming, leading to different effects on reaction time. Here, we applied qEEG to the latter testing paradigm. We have conducted a preliminary analysis, using data from the participants tested prior to interruption of the project by the Covid pandemic. Method: Participants (CH‐NAT, n=19; CH‐PAT, n=27) viewed a series of Stroop stimuli (e.g. the word "red" written in blue ink), and their task was either to respond to a given stimulus' color or its word content by pressing buttons. A trial consisted of two stimuli in sequence, and a masked subliminal priming word ("red" or "blue") was inserted between the two stimuli. The experimental focus was the second stimulus of each trial, which was characterized as having a task which was either switched or non‐switched compared to the first stimulus, and as having a desired response that was congruent or incongruent with the subliminal prime. Event‐related desynchronization (ERD) 250‐750 ms after the second stimulus was measured in the low‐ and high‐alpha bands (αERD). Result: αERD was observed in both high and low frequency bands following second‐stimulus presentation (both p<<<0.01, in all electrode groups). However there were no significant differences in αERD magnitude between congruent and incongruent prime conditions, nor between the CH‐NAT and CH‐PAT groups (all p>0.05). Conclusion: Comparisons of prime congruency may be complicated by the fact that the prime can be matched or mismatched along multiple dimensions (prime word, prime location, desired response, stimulus color, stimulus word). Given that behavioral effects have been found for this experimental paradigm, we expect that differences in neural activity may be revealed eventually with more participants, a wider exploratory analysis, and/or a refinement of the experiment task.